Metabolic pathway redundancy within the apicomplexan-dinoflagellate radiation argues against an ancient chromalveolate plastid. Issue 1 (2nd January 2016) - Waller, Ross F.; Gornik, Sebastian G.; Koreny, Ludek; Pain, Arnab
ABSTRACT: The chromalveolate hypothesis presents an attractively simple explanation for the presence of red algal-derived secondary plastids in 5 major eukaryotic lineages: "chromista" phyla, cryptophytes, haptophytes and ochrophytes; and alveolate phyla, dinoflagellates and apicomplexans. It posits that a single secondary endosymbiotic event occurred in a common ancestor of these diverse groups, and that this ancient plastid has since been maintained by vertical inheritance only. Substantial testing of this hypothesis by molecular phylogenies has, however, consistently failed to provide support for the predicted monophyly of the host organisms that harbour these plastids—the "chromalveolates." This lack of support does not disprove the chromalveolate hypothesis per se, but rather drives the proposed endosymbiosis deeper into the eukaryotic tree, and requires multiple plastid losses to have occurred within intervening aplastidic lineages. An alternative perspective on plastid evolution is offered by considering the metabolic partnership between the endosymbiont and its host cell. A recent analysis of metabolic pathways in a deep-branching dinoflagellate indicates a high level of pathway redundancy in the common ancestor of apicomplexans and dinoflagellates, and differential losses of these pathways soon after radiation of the major extant lineages. This suggests that vertical inheritance of an ancient plastid in alveolates is highly unlikely as it would necessitate maintenance of redundant pathways over very long evolutionary timescales.